Single-molecule visualization of human RECQ5 interactions with single-stranded DNA recombination intermediates. Issue 1 (17th December 2020) - Xue, Chaoyou; Molnarova, Lucia; Steinfeld, Justin B; Zhao, Weixing; Ma, Chujian; Spirek, Mario; Kaniecki, Kyle; Kwon, Youngho; Beláň, Ondrej; Krejci, Katerina; Boulton, Simon J; Sung, Patrick; et al.
Abstract: RECQ5 is one of five RecQ helicases found in humans and is thought to participate in homologous DNA recombination by acting as a negative regulator of the recombinase protein RAD51. Here, we use kinetic and single molecule imaging methods to monitor RECQ5 behavior on various nucleoprotein complexes. Our data demonstrate that RECQ5 can act as an ATP-dependent single-stranded DNA (ssDNA) motor protein and can translocate on ssDNA that is bound by replication protein A (RPA). RECQ5 can also translocate on RAD51-coated ssDNA and readily dismantles RAD51–ssDNA filaments. RECQ5 interacts with RAD51 through protein–protein contacts, and disruption of this interface through a RECQ5–F666A mutation reduces translocation velocity by ∼50%. However, RECQ5 readily removes the ATP hydrolysis-deficient mutant RAD51–K133R from ssDNA, suggesting that filament disruption is not coupled to the RAD51 ATP hydrolysis cycle. RECQ5 also readily removes RAD51–I287T, a RAD51 mutant with enhanced ssDNA-binding activity, from ssDNA. Surprisingly, RECQ5 can bind to double-stranded DNA (dsDNA), but it is unable to translocate. Similarly, RECQ5 cannot dismantle RAD51-bound heteroduplex joint molecules. Our results suggest that the roles of RECQ5 in genome maintenance may be regulated in part at the level of substrate specificity.